2015
DOI: 10.1002/jat.3157
|View full text |Cite
|
Sign up to set email alerts
|

mRNAs and miRNAs in whole blood associated with lung hyperplasia, fibrosis, and bronchiolo‐alveolar adenoma and adenocarcinoma after multi‐walled carbon nanotube inhalation exposure in mice

Abstract: Inhalation exposure to multi-walled carbon nanotubes (MWCNT) in mice results in inflammation, fibrosis, and the promotion of lung adenocarcinoma; however, the molecular basis behind these pathologies is unknown. This study determined global mRNA and miRNA profiles in whole blood from mice exposed by inhalation to MWCNT that correlated with the presence of lung hyperplasia, fibrosis, and bronchiolo-alveolar adenoma and adenocarcinoma. Six-week-old, male, B6C3F1 mice received a single intraperitoneal injection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 83 publications
0
39
0
1
Order By: Relevance
“…In a subsequent study of the same groups of mice studied in Sargent et al (2014), Snyder-Talkington et al (2016) observed increased expression of total mRNA and miRNA in the blood of the mice 17 months after exposure to MWCNT-7. In mice that developed pathological changes in the lungs – including hyperplasia, fibrosis, bronchiolo-alveolar adenoma, and bronchiolo-alveolar carcinoma – after the MCA/corn oil administration followed by MWCNT/air inhalation, numerous mRNAs and miRNAs in the blood were significantly up- or down-regulated (Snyder-Talkington et al 2016).…”
Section: Indirect Genotoxicity Of Cnts and Cnfs: Rodent Studiesmentioning
confidence: 88%
See 2 more Smart Citations
“…In a subsequent study of the same groups of mice studied in Sargent et al (2014), Snyder-Talkington et al (2016) observed increased expression of total mRNA and miRNA in the blood of the mice 17 months after exposure to MWCNT-7. In mice that developed pathological changes in the lungs – including hyperplasia, fibrosis, bronchiolo-alveolar adenoma, and bronchiolo-alveolar carcinoma – after the MCA/corn oil administration followed by MWCNT/air inhalation, numerous mRNAs and miRNAs in the blood were significantly up- or down-regulated (Snyder-Talkington et al 2016).…”
Section: Indirect Genotoxicity Of Cnts and Cnfs: Rodent Studiesmentioning
confidence: 88%
“…In mice that developed pathological changes in the lungs – including hyperplasia, fibrosis, bronchiolo-alveolar adenoma, and bronchiolo-alveolar carcinoma – after the MCA/corn oil administration followed by MWCNT/air inhalation, numerous mRNAs and miRNAs in the blood were significantly up- or down-regulated (Snyder-Talkington et al 2016). For a given pathology, the expression profile was different between the exposure groups, suggesting a specific response to the different exposures.…”
Section: Indirect Genotoxicity Of Cnts and Cnfs: Rodent Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be emphasized that the MWCNT exposed workers investigated as a part of this study are all males, have various exposure regimes and have only spent about ~1–3 years working at the facility. In fact, the upregulation of TGF-β1 and OPN upon exposure to MWCNTs was not always consistent and depended on several experimental factors including CNT characteristics, animal gender, concentration, exposure type and time points employed in each study (Porter et al, 2010; Dymacek et al, 2015; Khaliullin et al, 2015; Poulsen et al, 2015; Snyder-Talkington et al, 2015; Snyder-Talkington et al, 2016). A larger cohort of workers exposed to MWCNTs during life-time employment would provide a more accurate validation of realistic markers by simultaneously comparing nasal lavage, sputum and serum.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was shown that exposure to MWCNT activated TGF-b/Smad signaling pathway in fibroblasts and myofibroblasts thus facilitating pulmonary fibrosis (Wang et al, 2015). Moreover, inhalation exposure to MWCNT promotes the growth and neoplastic progression of initiated lung cells in mice (Sargent et al, 2014; Snyder-Talkington et al, 2016). These effects were observed at a dose of 31.2 µg/mouse – that is achievable in human exposures in occupational settings (Erdely et al, 2013; Khaliullin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%